Penerapan Metode Weighted Moving Average dalam Meramalkan Penjualan Minuman Kekinian di Café - Qomaruzzaman; Fahmi, Yusril; Agustin, Soffiana (Fakultas Teknik Universitas Nahdlatul Ulama Sumatera Barat, 2025)
The trend of modern beverages has grown significantly in recent years, in line with changes in people's lifestyles. However, despite their popularity, café business owners often face challenges due to fluctuating sales every month. This condition directly affects inventory management and daily production planning. To address this issue, accurate sales forecasting is needed. This study aims to forecast the sales of Kayyoman Macchiato using the Weighted Moving Average (WMA) method with a weight ratio of 1:1:5. The data used consists of monthly sales records from January 2020 to April 2025. After the forecasting process, the results were analyzed using three indicators: MAD, MSE, and MAPE. The findings show a MAD of 31.78, MSE of 1,496.13, and MAPE of 16.14%. These results indicate that the prediction accuracy falls into the